A phenomenological study on father involvement in family therapy sessions - Doğu, İlayda (İstanbul Bilgi Üniversitesi, 2020)
ABSTRACT: This thesis consists of two articles. The first article is a literature review of fatherhood research. The article includes discussions about gender roles and fatherhood, fatherhood in Turkish culture, and men in therapy. The second article includes a brief literature review on father involvement in child development and family therapy sessions and extends the literature conducting a qualitative study aiming to understand the experiences of fathers who are involved in family therapy sessions and also the experiences of therapists who are working with these fathers in a therapeutic context. Five fathers and five therapists were interviewed and the data were analyzed using Interpretive Phenomenological Analysis and revealed four themes for fathers: (a) What brings fathers to the therapy room? (b) How do fathers see therapy? (c) Expectations from the therapist, (d) Becoming a father; A life-changing experience and five themes for therapists: (a) Value of fathers in family therapy, (b) Difficulty of engaging the fathers, (c) Therapists’ ways to include fathers, (d) Why do fathers come to therapy? (e) Family-of-origin experiences. The findings are discussed in relation to the current fatherhood literature and clinical implications are outlined for clinicians who work with fathers.

ÖZET: Bu tez iki makaleden oluşmaktadır. Birinci makale babalık araştırmaları hakkında bir literatür taraması içermektedir. Makalenin içinde cinsiyet rolleri ve babalık, Türk kültüründe babalık ve terapide erkekler gibi konular tartışılmıştır. İkinci makale babaların çocuk gelişimine ve aile terapisine katılımına dair kısa bir literatür taraması içermekte ve kalitatif bir metotla aile terapisine katılan babaların deneyimlerinin ve bu babalarla terapötik bir düzlemde çalışan terapistlerin deneyimlerinin anlaşılmasını hedefleyerek literatürü genişletmektedir. Aile terapisine katılan beş baba ve beş terapistle yapılan birebir görüşmelerden elde edilen veriler Yorumlayıcı Fenomenolojik Analiz yöntemiyle incelenmiş ve babalar için dört tema ortaya çıkmıştır: (a) babaları terapi odasına ne getiriyor? (b) babalar terapiyi nasıl görüyor? (c) terapistten beklentiler, (d) baba olmak; dönüştürücü bir deneyim, ve terapistler için de beş tema ortaya çıkmıştır: (a) aile terapisinde babanın değeri, (b) babaları katmanın zorluğu, (c) babaları katarken terapistin yöntemleri, (d) babalar neden terapiye geliyor? (e) kök aile deneyimleri. Sonuçlar güncel babalık literatürüyle bağ kurularak tartışılmış ve babalarla çalışan klinisyenler için öneriler sunulmuştur.
Babaların aile terapisine katılımı üzerine fenomenolojik bir çalışma
Keywords: father involvement; family therapy; psychotherapy; gender roles; Interpretive Phenomenological Analysis; baba katılımı; aile terapisi; psikoterapi; cinsiyet roller; Yorumlayıcı Fenomenolojik Analiz